Gender accommodative versus transformative approaches: a comparative assessment within a post-harvest fish loss reduction intervention - Cole, Steven M.; Kaminski, A.M.; McDougall, C.; Kefi, A.S.; Marinda, P.A.; Maliko, M.; Mtonga, J. (Informa UK Limited, 2020)
Technical and social constraints limit value chain actors from equitably engaging in and benefiting from capture fisheries in low-income settings. Extension and development programs often focus on the former, which reflects a technocratic orientation of the fisheries sector and uncertainty about effective ways for development programs to engage with gender and other social constraints. This study presents empirical insights that address these challenges to fisheries development. The study took place in fishing camps in the Barotse Floodplain, Zambia to compare two approaches addressing gender constraints within a broader post-harvest fish loss reduction intervention: an accommodative and a transformative approach. The former embodied a more common ‘practical needs’ set of strategies to ensure female participation, while the latter comprised a communication tool embedded in an action research process to build critical consciousness. Results indicate that the use of a transformative approach led to significant changes in gender equal attitudes and women’s empowerment outcomes compared to only using an accommodative approach. Development programs working in fisheries can apply the findings to engage effectively with gender constraints, especially using transformative approaches to help enable women and men to overcome the social and technical barriers that constrain their lives and livelihoods.